Analyze the VANET performance in presence of timing attack and sinkhole attack using OMNeT++ - Bhatti, F. N.; Ahmad, R. B.; Abu Bakar, Muhamad Shahbani; Daud, Shuhaizar; Elias, S. J.; Warip, M. N. M. (Akademia Baru, 2015)
The growth in research advancement of vehicular Adhoc Network (VANET) has seen a significant rise in the security attack.In this paper, we give the simulation for quantitative investigate of VANET in the presence of Timing attack and Sinkhole attack.We described the performance metrics and discover the effect and harm caused by Timing attack and Sinkhole attack, which directly affect the network Quality of Service (QoS).Our assessment results show that the impact on VANET under Timing attack and Sinkhole attack varies potentially depending on a number of vehicles, the number of attacker vehicles.The impact of a Timing attack and Sinkhole attack increased significantly by increasing the number of attacker vehicles in several of the situations.While the number of attacks impact level continually effect on network performance with varying the number of vehicles.The contribution in this paper has used the OMNeT++ simulators to quantify analysis of the VANET performance in the presence of attacks by comparison with a non-malicious network and a network which enclosed malicious behavior.It has been investigated in two types of attacks, namely 1. Sinkhole attack 2. Timing attack.